Epstein-Barr Virus–Associated Smooth-Muscle Tumor of the Brain - Alfalahi, Afra; Omar, Abdelsimar Il; Fox, Krystal; Spears, Julian; Sharma, Malika; Bharatha, Aditya; Munoz, David G.; Suthiphosuwan, Suradech (American Journal of Neuroradiology, 2024)
Epstein-Barr virus, a herpesvirus, has been associated with a variety of cancers, including Burkitt, Hodgkin, and non-Hodgkin lymphomas; posttransplant lymphoproliferative disorders; gastric carcinoma; and nasopharyngeal carcinoma, in both immunocompetent and immunocompromised individuals. Previous studies have established a connection between Epstein-Barr virus and the development of smooth-muscle tumors. Smooth-muscle tumors of the brain are very rare and are often misdiagnosed as meningiomas on imaging. To our knowledge, advanced imaging findings such as MR perfusion of smooth-muscle tumors of the brain have never been reported. We describe the radiologic and pathologic features of the Epstein-Barr virus–associated smooth-muscle tumors of the brain in a person with newly diagnosed advanced HIV.EBVEpstein-Barr virusEBV-SMTEpstein-Barr virus–associated smooth-muscle tumorrCBVrelative CBVSMTsmooth-muscle tumor